2007
DOI: 10.1002/elps.200600450
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing doxorubicin‐induced apoptosis in HepG2 cells using an integrated microfluidic device

Abstract: Apoptosis has now established its importance in numerous areas of biology and is recently receiving great attention as an important topic related to the development of diseases. In this work, an integrated microfluidic device was developed to characterize doxorubicin-induced apoptosis in human hepatocellular carcinoma (HepG2) cells. A continuous concentration gradient of stimulator (doxorubicin) was generated in the upstream network and used to perfuse downstream cultured HepG2 cells. The appropriate fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 24 publications
(28 reference statements)
3
34
0
1
Order By: Relevance
“…2͑c͒, it was found that the experimental data were correlated well with the theoretical prediction, 30 and the central parts of channels with more errors presumably ascribed to the hydraulic defocusing at the merged points. 42 By comparing with previous similar works, 37,42 the data obtained here matched them well.…”
Section: A Design and Characterization Of The Integrated Microdevicesupporting
confidence: 87%
See 1 more Smart Citation
“…2͑c͒, it was found that the experimental data were correlated well with the theoretical prediction, 30 and the central parts of channels with more errors presumably ascribed to the hydraulic defocusing at the merged points. 42 By comparing with previous similar works, 37,42 the data obtained here matched them well.…”
Section: A Design and Characterization Of The Integrated Microdevicesupporting
confidence: 87%
“…This property contributed to the stable position of embryos under the flowing system, and enabled the microfluidic chip that applied in fish embryo-associated assay to be used repeatedly comparable to the microdevice for cell-based assay. 37 In the tests, we placed the microfluidic device at an angle of about 20°to horizontal level to facilitate the withdrawal of waste without additional use of tubes, and the open culture chamber can still maintain the normoxia development for embryos that was particularly important for larvae. 38 The open surface design together with gradient soluble molecules were not only wellsuited for cell-based research, 39 but benefited zebrafish embryo-related investigation that even did not need a CO 2 culture incubator.…”
Section: A Design and Characterization Of The Integrated Microdevicementioning
confidence: 99%
“…Although the gradient system showed sensitivity and specificity similar to those found in a multiwell system, it had several advantages compared to conventional multiwell system and previously developed microfluidic-based gradient generators, [34][35][36] including the short time required for gradient generation, low cost, highthroughput bioanalytical assays, and small amount of biological target and drug candidates. The system also offered features such as simplicity of design, portability, and fast operation.…”
Section: Mechanism Of Cell Death In Response To the 6-ohda Gradientsmentioning
confidence: 99%
“…The tree-like microstructure 22 to generate different concentration gradients is a useful design to improve the throughput and has been used to study gene expression, cell response to stimuli and cell-based cancer drug screening. [23][24][25][26] The high-throughput capability of this design also makes microfluidic chip an attractive platform for the study of virus infection mechanism.…”
Section: Introductionmentioning
confidence: 99%